Citric acid functionalized cellulose monolith for continuous‐flow removal of cationic dye in water - Zhengtian Xie; Linxuan Li; Yu‐I Hsu; Taka‐Aki Asoh; Hiroshi Uyama (Nano Select, 2022)
Abstract Developing efficient yet cost‐effective material from bioresources for dye removal is promising in both economic and environmental protection aspects. Here, a monolithic cellulose material functionalized with citric acid is reported as an absorbent for continuous‐flow removal of cationic dye. The functionalization process is realized by a direct esterification reaction between citric acid and cellulose without any other additions. The obtained monolithic absorbent possesses a 3D connected porous structure, which enables the application of the product in a continuous‐flow fashion. Results indicate that the produced monolith has a good adsorption ability to methylene blue. Moreover, the product can be reused after a fast desorption process by flowing with a salt solution. This work provides a simple strategy for fabricating green absorbents based on biofriendly cellulose and citric acid, which exhibits a potential of industrial application for water treatment.